Ilha dos Búzios, Litoral Norte do Estado de São Paulo: aspectos geológicos e petrográficos - Alves, Francisco R.; Gomes, Celso B. (Geologia USP. Série Científica, 2001)
Cretaceous syenitic rock-types intruded into Precambrian charnockites characterize the geology of Búzios island (7.5 km²) in area off the northern coast of the State of São Paulo, SE Brazil. Both lithologic units are cut by a large number of dykes, mostly NE-trending and quite variable in composition. The syenites may include charnockitic and mafic rock xenoliths and also contain quartz-filled, irregular miarolitic cavities. The alkaline rocks, corresponding to approximately 90% of the whole island, are dominantly coarse-grained and range in composition from alkali feldspar syenites to quartz-alkali feldspar syenites. Locally, fine-grained syenitic types are also found. Dykes are widespread over the island and can be placed into the felsic group, which includes lithologies varying from phonolites to trachytes to rhyolites (microgranites), or into the mafic-ultramafic group, the latter mainly consisting of diabases, microdiorites and lamprophyres. Alkali feldspar (micromesoperthite with slight dominance of albititic phases) is the most abundant mineral in syenitic rocks. Additional components are clinopyroxene (diopside-augite ranging to aegirine-augite), commonly replaced by amphibole/biotite, and opaques (magnetite, ilmenite), with apatite, sphene and zircon as accessories. The felsic dykes may contain other feldspars (sanidine and albite) either as micro- to phenocrysts or as groundmass phases; feldspathoids (nepheline, sodalite) are also found in some microsyenites. The mafic-ultramafic dykes, in particular the lamprophyres, are mainly characterized by a primary mineral assemblage consisting of olivine, clinopyroxene (titanian augite) and amphibole (kaersutite), besides a groundmass bearing glassy material and analcite. Also to be noted in the lamprophyres is the presence of small grains or aggregates of carbonate ocelli as primary phases. Dykes showing a more basaltic composition have zoned plagioclase (andesine-labradorite), interstitial alkali feldspar and, as main ferromagnesian minerals, clinopyroxene (diopside-augite), amphibole, biotite and opaques. In spite of the petrographic and chemical differences, the alkaline bodies forming the islands of Vitória, Búzios, São Sebastião and Monte de Trigo, all found off the northern coast of the State of São Paulo, seem to be part of magmatic events related to the same geologic setting. They probably represent contemporaneous intrusions derived from an anomalously hot mantle and are closely associated with the Mesozoic tectonic evolution of Southern Brazil.